Turismo sob a ótica da sustentabilidade - Santos, Cristiane Alcântara de Jesus (Boletim Técnico do Senac, 2004)
Discussion of sustainable development and the role of tourism has grown more intense over the last few years, with the activity of tourism becoming a key - and sometimes sole - factor in dynamizing and introducing regions and even countries to the map of spatial consumption. Accordingly, maintaining or even seeking sustainability has turned into a basic instrument for guiding tourist policies, planning and management based on economic efficiency, social equality and environmental conservation. This relies especially on the complementary nature of the public and private sectors, based in turn on the participation of citizens and aimed at promoting some bases for development.